Nonsteroidal anti-inflammatory drugs, gastroprotection, and benefit-risk. - Moore, R; Derry, S; Simon, L; Emery, P (2014)
BACKGROUND: Gastroprotective agents (GPA) substantially reduce morbidity and mortality with long-term nonsteroidal anti-inflammatory drugs (NSAIDs) and aspirin. OBJECTIVE: To evaluate efficacy of NSAIDs, protection against NSAID-induced gastrointestinal harm, and balance of benefit and risk. METHODS: Free text searches of PubMed (December 2012) supplemented with "related citation" and "cited by" facilities on PubMed and Google Scholar for patient requirements, NSAID effectiveness, pain relief benefits, gastroprotective strategies, adherence to gastroprotection prescribing, and serious harm with NSAIDs and GPA. RESULTS: Patients want 50% reduction in pain intensity and improved fatigue, distress, and quality of life. Meta-analyses of NSAID trials in musculoskeletal conditions had bimodal responses with good pain relief or little. Number needed to treat (NNTs) for good pain relief were 3 to 9. Proton pump inhibitors (PPI) and high-dose histamine-2 receptor antagonists (H2 RA) provided similar gastroprotection, with no conclusive evidence of greater PPI efficacy compared with high-dose H2 RA. Prescriber adherence to guidance on use of GPA with NSAIDS was 49% in studies published since 2005; patient adherence was less than 100%. PPI use at higher doses over longer periods is associated with increased risk of serious adverse events, including fracture; no such evidence was found for H2 RA. Patients with chronic conditions are more willing to accept risk of harm for successful treatment than their physicians. CONCLUSION: Guidance on NSAIDs use should ensure that patients have a good level of pain relief and that gastroprotection is guaranteed for the NSAID delivering good pain relief. Fixed-dose combinations of NSAID plus GPA offer one solution.